2008
DOI: 10.1016/j.jcrs.2007.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ciliary sulcus diameter measured by 35 MHz ultrasound biomicroscopy and other ocular measurements

Abstract: Mean corneal curvature was significantly and negatively correlated with horizontal sulcus diameter. The derived regression formula based on mean corneal curvature measurements may help predict sulcus diameters for proper sizing of posterior chamber phakic intraocular lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 17 publications
2
26
0
1
Order By: Relevance
“…Kim et al 16 found a high negative correlation (r Z À0.865) between K readings (in diopters) and the sulcus diameter; however, the study was limited by the number of patients (n Z 14), that accommodation was not excluded, and that most of the patients were highly myopic. In our study of pseudophakic eyes, K readings and AL showed a weak correlation with sulcus diameter.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Kim et al 16 found a high negative correlation (r Z À0.865) between K readings (in diopters) and the sulcus diameter; however, the study was limited by the number of patients (n Z 14), that accommodation was not excluded, and that most of the patients were highly myopic. In our study of pseudophakic eyes, K readings and AL showed a weak correlation with sulcus diameter.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies [15][16][17][18][19] have evaluated the relationship between WTW and STS diameters in an effort to select adequately sized posterior phakic IOLs. Using different devices to measure the STS and the WTW, they showed a weak correlation (r Z 0.406 to r Z 0.597) between these 2 values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies [4][5][6][7] found no correlation between WTW diameter and ciliary sulcus diameter, and others found a WTW diameter larger than the ciliary sulcus diameter. 5,8 Choi et al 3 found high vault (O750 mm) and low vault (!250 mm) in 17.6% and 23.5% of eyes, respectively, when determining pIOL length using WTW diameter. These conflicting results could be due to individual variation in WTW diameter and ciliary sulcus diameter and the repeatability performance of the measuring device.…”
Section: Online-only Materialsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Despite efforts to improve predictability of vault following ICL implantation, it remains poor; the reasons for this are multiple. 5,[13][14][15][16][17][18][19][20][21][22][23] High-frequency ultrasound biomicroscopy (UBM) with a wide scanning field has enabled direct measurement of horizontal sulcus-to-sulcus (STS) diameter. Poor correspondence (г<0.50) between the horizontal WTW and STS measure has since been reported, however the width of the limits of agreement (LoA) reported between horizontal WTW and STS measures is similar to repeatability limits of STS estimates.…”
Section: Introductionmentioning
confidence: 99%